Formação socioespacial da cidade Delmiro Gouveia/AL: um estudo sobre a Fábrica da Pedra na configuração do espaço urbano - Cruz, Camila Rodrigues da (2024)
The study of the socio-spatial formation of the city of Delmiro Gouveia (1914-2017) requires a process analysis of the constitution of the city, which had in the installation of the Fábrica da Pedra the defining element of social and economic relations imprinted on the urban space of this city in the interior of the State of Alagoas. This research studies the configuration of the city from the installation of the factory and after its closure, a fact that triggered changes in form and content in the organization of space, as well as in the lives of residents and workers. Furthermore, this paper understands that the activities of the Fábrica da Pedra during the period of its operation between 1914 and 2017, more than a century, are indispensable for the analysis of the relations that formed the city of Delmiro Gouveia/AL. The period was defined from the establishment of the textile industry in Pedra (in 1914), founded by Delmiro Augusto da Cruz Gouveia, from Ceará, and after the closure of this factory in 2017. The aim of this qualitative research was to analyze the territorial formation of Delmiro Gouveia, as well as the connections that explain the city’s place in the capitalist expansion in the Northeast and Brazil. The results of the research show that the intervention in the space that today corresponds to the city of Delmiro Gouveia is part of the scenario of exploitation of Alagoas and the Northeastern Sertão, considering the subordination to capital in the process of historical development of the Brazilian economy — externally and internally. With this research, we hope to have contributed to an understanding of the capitalist production of space, considering how the city in question was inserted into the process of capital accumulation at the beginning of the 20th century — when the international division of labor was reshaped and, consequently, changed the way in which the reproduction of capital was done internally in Brazil.